Implementação de um sistema de gestão da qualidade em escritórios de projeto arquitetônico de pequeno porte. - Camila Veiga de Souza (2008)
This study aims, in addition to the theoretical arguments, define and present a quality management system applied to the design process of an design office based on the plan proposed by the Quality Sector of Melhado and Cambiaghi , which was set as a normative reference to the qualification of companies to design, implement and test in an office of architectural project of small and analyse the impact of the system in thisoffice and four other design companies that have opted for implementation of similar system. The implementation of a SGQ can lead firms to project the higher levels of competitiveness and ensure improvement in the efficiency of the process of project, in attendance to the needs of customers and continuous improvement of processes,products and services. As a way to reach the standardization of procedures for abetter definition of the parameters in search of the quality of their processes and to meet any requirements of contractors especially when it comes to public agencies or donors, programmes and systems of quality management in enterprises of the construction civilian have been implemented based on standards NBR / ISO 90001:2000. However, the recent literature indicates that the applicability of thestandard creates doubts, to be the best option for implementing a SGQ offices in the project, particularly in small offices of the architectural project focused because they are not perfectly adapted to the reality of offices project, mainly companies from small businesses, by prioritizing the understanding of the project as a product, instead of considering it as a service or process that needs to be managed and also to presentrequirements deemed unnecessary businesses of project, not interfering in the quality of the process itself or in the project management system of the enterprise process. A SGQ aimed to companies from project to be sufficiently efficient to meet the needs of the parties concerned with the dynamics of the process of the project in addition to setting up as a tool for evaluation and validation of project-product and systematization of steps, structuring your best development and increasing the control of the process, and provide guidelines that the process dealing with that this leads to any form of bureaucracy exacerbated.